Work culture and employee performance in generation z: the mediating role of psychological well-being - Karisma Karisma; Rahmad Firdaus; Suhardi Suhardi (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the influence of organizational behavior, work motivation, and work culture on the performance of Generation Z employees in the Pangkalpinang Regional Government, with psychological well-being as a moderating variable. Using a quantitative approach and Partial Least Square (PLS-SEM) analysis, this study involved young civil servants to understand the dynamics of their productivity. The results show that work culture has a positive and significant influence on employee performance, both directly and indirectly through psychological well-being. In contrast, organizational behavior and work motivation do not show a significant impact on performance directly. These findings confirm that for Generation Z, a supportive work environment and stable mental health are the main determinants in achieving work efficiency. The implications of this study suggest that local government agencies undertake a more inclusive work culture transformation and pay attention to employee psychological well-being as a strategy to improve bureaucratic performance.